PSYCHOLOGICAL ANALYSIS ON THE IMPACT OF DEPRESSION IN STEINBECK’S OF MICE AND MEN - Tonapa, Natanael; Lolowang, Imelda S.; Rorimpandey, Rinny S. (SoCul: International Journal of Research in Social Cultural Issues, 2024)
The present study aims at investigating the symptoms and the impact of depression experienced by Lennie Small, the main character in Steinbeck’s Of Mice and Men. This research is in the form of words which means this research was done qualitatively. The data comes from the novel Of Mice and Men which was written by John Steinbeck in 1937. The data were collected by reading thoroughly the novel and taking notes about the evidences of the impact of depression. In administering this research, psychological approach was used as data analysis method in order to discover the symptoms of depression of Lennie Small. The result of the study explains that Lennie had several symptoms of depression, they are; 7 symptoms of sadness, 8 symptoms of helplessness and 5 symptoms of worthlessness. The impact of each symptom made the depression to become worse and elevated to the next level of depression, at the first place it started with sadness then elevated to helplessness then to worthlessness, which in the end took the life of Lennie Small. It can be concluded that Lennie Small did have symptoms of depression which is shown throughout the story. This research hopefully could assist people in learning the symptoms of depression and become a reference for those who wants to research about depression.